2014
DOI: 10.7314/apjcp.2014.15.10.4159
|View full text |Cite
|
Sign up to set email alerts
|

Etoposide-Cisplatin Alternating with Vinorelbine-Cisplatin Versus Etoposide-Cisplatin Alone in Patients with Extensive Disease Combined with Small Cell Lung Cancer

Abstract: Background: The aim of this study was to evaluate the efficacy of alternating etoposide-cisplatin and vinorelbine-cisplatin (EP-NP) compared with an etoposide-cisplatin (EP) regimen for advanced combined small cell carcinomas. Materials and Methods: Histologically confirmed combined small cell carcinoma patients who met the inclusion criteria were randomly assigned (1:1) into either the EP-NP setting (group A) or the EP setting (group B). The primary endpoint was progression-free survival in patients who recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
(34 reference statements)
1
9
0
Order By: Relevance
“…In this study, acceptable toxicity values were found when the results were compared with those from other studies (10,13).…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…In this study, acceptable toxicity values were found when the results were compared with those from other studies (10,13).…”
Section: Discussionsupporting
confidence: 50%
“…These results suggest that RT is effective for the patients who do not shown a good response to CT despite the different reported results in the literature (5,31). The response rates to CT for SCLC were 60-95% in many studies (6,4,10,5). However, the total response rate to CT was 45% in our study because these patients were sent from other clinics after disease progression or bad results of CT.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Combined small cell lung cancer (C-SCLC) is defined as a subgroup of small cell lung cancers (SCLC), which accounts for 2-28 % of all SCLC [1][2][3][4]. According to the NCCN guidelines, the diagnosis of C-SCLC is based on the result that any non-small cell components are more than 10 % of the SCLC tumors [5].…”
Section: Introductionmentioning
confidence: 99%
“…In general, patients were treated with "sandwich treatment", namely "induction chemother apy+radiotherapy+consolidate chemotherapy" (Tsujino et al, 2014). Standard combination chemotherapy regimens were "VP-16+DDP" recommended by the NCCN guidelines, according to the tolerance to chemotherapy in patients with 4-6 cycles (Ha et al, 2013;Zhang et al, 2014). In view of the important significance of PCI on the prognosis of patients with small cell lung cancer, patients who reach CR by the treatment of radiotherapy and chemotherapy should accepted PCI (25Gy/10F/2W) (Simon et al, 2007).…”
Section: Principles Of Treatmentmentioning
confidence: 99%